2010
DOI: 10.1242/jcs.067330
|View full text |Cite
|
Sign up to set email alerts
|

Heteromultimeric TRPML channel assemblies play a crucial role in the regulation of cell viability models and starvation-induced autophagy

Abstract: SummaryThe mucolipin (TRPML) subfamily of transient receptor potential (TRP) cation channels consists of three members that play various roles in the regulation of membrane and protein sorting along endo-lysosomal pathways. Loss-of-function mutations in TRPML1 cause the neurodegenerative lysosomal storage disorder, mucolipidosis type IV (MLIV), whereas a gain-of-function mutation in TRPML3 is principally implicated in the hearing-impaired and abnormally pigmented varitint-waddler mouse. Currently, TRPML2 is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 49 publications
2
49
0
Order By: Relevance
“…TRPML channels are able to heteromultimerize with each other. This has been shown by different groups (Venkatachalam et al, 2006;Zeevi et al, 2009Zeevi et al, , 2010Curcio-Morelli et al, 2010;Grimm et al, 2010). In addition, in vitro TRPML1/TRPML3 coexpression experiments indicated that TRPML1 is able to suppress TRPML3 activation by small-molecule agonists .…”
Section: Trpml Channels and Tpcs In Endolysosomal Cation Homeostasis 239mentioning
confidence: 61%
“…TRPML channels are able to heteromultimerize with each other. This has been shown by different groups (Venkatachalam et al, 2006;Zeevi et al, 2009Zeevi et al, , 2010Curcio-Morelli et al, 2010;Grimm et al, 2010). In addition, in vitro TRPML1/TRPML3 coexpression experiments indicated that TRPML1 is able to suppress TRPML3 activation by small-molecule agonists .…”
Section: Trpml Channels and Tpcs In Endolysosomal Cation Homeostasis 239mentioning
confidence: 61%
“…In recent years, TRPML1 has been characterized using electrophysiological tools and its basic cation channel properties have been investigated [9][10][11][12][13][14][15][16][17][18][19] , its protein-protein interaction network has been explored [20][21][22][23][24] , and knockout mouse models have been generated and investigated [25][26][27][28] . However, effective treatment options for MLIV patients are still missing.…”
mentioning
confidence: 99%
“…NAADP as a potent Ca 2+ mobilizing messenger, which targets the TRPMLs or TPCs and triggers Ca 2+ release from the endolysosomal stores [19]. As we known, the members of the TRPML constitute a family of evolutionarily conserved cation channels that play crucial roles in endolysosomal vesicles [20] [49]. TRPMLs localize to endolysosomes and facilitate Ca 2+ -dependent fusion between autophagosomes and lysosomes resulting in lysosomal degradation of autophagic material [20].…”
Section: The Negative Regulation Of Cd38 In Autophagymentioning
confidence: 99%